A Realistic Lightweight Anonymous Authentication Protocol for Securing Real-Time Application Data Access in Wireless Sensor Networks - Gope, Prosanta; Tzonelih Hwang (IEEE transactions on industrial electronics (1982), 2016)
User authentication in wireless sensor networks (WSN) is a critical security issue due to their unattended and hostile deployment in the field. Since the sensor nodes are equipped with limited computing power, storage, and communication modules, authenticating remote users in such resource-constrained environment is a paramount security concern. Until now, impressive efforts have been made for designing authentication schemes with user anonymity by using only the lightweight cryptographic primitives, such as symmetric key encryption/decryption and hash functions. However, to the best of our knowledge, none has succeeded so far. In this paper, we take an initial step to shed light on the rationale underlying this prominent issue. In order to do that here at first, we demonstrate that the existing solutions for anonymous user authentication in WSN are impractical. Subsequently, we propose a realistic authentication protocol for WSN, which can ensure various imperative security properties like user anonymity, untraceability, forward/backward secrecy, perfect forward secrecy, etc.